"Handing out non-prescribed antibiotics is storing up trouble for the next generation!" Unpacking multistakeholder views of drivers and potential solutions in Ethiopia - Sewunet Admasu Belachew; Lisa Hall; Linda A Selvey (BMC, 2023)
Abstract Background Antibiotic resistance is a global health crisis, with inappropriate antibiotic use often being linked to non-prescribed antibiotic dispensing practices. This study aimed to examine the perspectives of multiple stakeholders on the drivers and potential solutions for non-prescribed antibiotic dispensing in Ethiopian community drug retail outlets (CDROs). Despite the prescription only use policies, the practice remains prevalent in Ethiopia. Many factors are thought to contribute to this issue, although little research is available for non-urban settings. Methods A phenomenological qualitative study was conducted. Pharmacy professionals (owners or employees) working in non-urban towns CDROs were selected through a simulated client study, which identified CDROs that had dispensed antibiotics without a prescription. Some high-level decision makers in the Ethiopian health system were also purposively selected. Interviews were conducted in-person and over the phone or via Zoom. The interview data were transcribed verbatim, translated to English, and thematically analysed. NVivo 12 software was used to assist with coding. Results CDRO pharmacy professionals (n = 18) and five decision makers were interviewed. Most professionals (61%) were pharmacists working in drug stores, with one to 11 years of work experience. Several contributing factors were identified at the level of patients, CDRO staff, and the healthcare system. These included economic interests, inadequate knowledge and inappropriate attitudes about antibiotic use or supply, and issues within the healthcare system included inaccessibility and insufficient capacity, absence of or a weak enforcement of prescription-only regulations or service supervision. Additionally, patient-related factors included a lack of knowledge and inappropriate attitudes about antibiotics use and their supply, previous successful treatment experience and a culture of seeking out antibiotics. Conclusions A complex set of modifiable factors related to patients, CDRO staff and healthcare system were identified that contribute to the non-prescribed supply of antibiotics. Due to this complexity, a single solution will not resolve the issues. Therefore, a range of multifaceted solutions have been suggested, including stricter regulation, increasing availability and accessibility of healthcare services, collaboration, and local consensus-building among CDROs, regular training for CDRO staff, and using community social events to educate the public about responsible use of antibiotics.